Non-ag. strep.-infected dairy cows (environmental strep.) - Kirk, John; Mellenberger, Roger (University of Minnesota. Agricultural Extension Service, 1990)
This archival publication may not reflect current scientific knowledge or recommendations. Current information available from the University of Minnesota Extension: https://www.extension.umn.edu.
1 online resource (PDF, 4 pages)